Satricum – Scavi e reperti archeologici. Exhibition in Le Ferriere, province of Latina, Italy, 201-2017 and M. Gnade (ed.), 2007. Satricum. Trenta anni di scavi olandesi, Amsterdam: Amsterdams Archeologisch Centrum, Universiteit van Amsterdam - Steensma, Niels (Ex Novo: Journal of Archaeology, 2016)
Satricum – Scavi e reperti archeologici. Exhibition in Le Ferriere, province of Latina, Italy, 11 June 2014 – 11 January 2015 (prolonged until 1 June 2017) and Gnade (ed.), 2007. Satricum. Trenta anni di scavi olandesi, Amsterdam: Amsterdams Archeologisch Centrum, Universiteit van Amsterdam. ISBN 978-90-78863-14-4. 208 pp., €25,00